Assessment of neutrophil and neutrophil/lymphocyte ratio in coronary collateral developed patients with acute coronary syndrome - Mansiroglu,Asli Kurtar (2020)
SUMMARY OBJECTIVE Inflammation-related markers provide diagnostic and prognostic information for coronary artery disease and acute coronary syndrome. We aimed to compare neutrophil count and neutrophil/lymphocyte ratio (NLR) in acute coronary syndrome patients with coronary collateral development in our study. METHODS A total of 426 patients (102 unstable angina pectoris (USAP), 223 non-ST-elevation myocardial infarction (non-STEMI), 103 ST-elevation myocardial infarction (STEMI) were compared regarding hemoglobin, platelet, lymphocyte, neutrophil count, and NLR. RESULTS Neutrophil count and NLR were significantly lower in USAP patients and higher in STEMI patients; 5.14± 1.79 vs. 7.21± 3.05 vs. 9.93±4.67 and 2.92±2.39 vs. 5.19±4.80 vs. 7.93±6.38, p <0.001. Other parameters, i.e., hemoglobin, platelet, and lymphocyte count, were not significantly different between the groups. CONCLUSIONS In our study, it was concluded that there may be a statistically significant difference in the number of neutrophil counts and NLR among the types of acute coronary syndromes with coronary collateral development.